CARACTERÍSTICAS FÍSICO-HÍDRICAS DO SOLO SUBMETIDO A DIFERENTES MANEJOS, EM AQUIDAUANA-MS - Ferrari, João Victor; Lopes, Adriano; Pontim, João Pedro; Rodrigues, Felipe; Do Val, Carla (ANAIS DO ENIC, 2018)
-